Aassociation between physical activity and body mass index in the civilian chemical victims of Sardasht 20 years after sulfur mustard exposure - Z. Ghazanfari; T. Ghazanfari; R. Yaraee; R. Amini; S. Ghaderi; A. Pirasteh; S. Moaiedmohseni; M. Naghizadeh; S. Faghihzadeh (Afarand Scholarly Publishing Institute, 2009)
Background: Physical activity has two important therapeutic goals including providing health and prevention of secondary diseases for chemical victims. Identification of the effective factors on physical activity specifically factors decreasing physical activity and caring them by patients & care providers can effective in chemical victim's health promotion. In this study, the self reported physical activity of chemical victims, 20 years after sulfur mustard exposure, and its potential association with BMI was investigated Patients and Methods: In this research, that was a cross-sectional study, self-reported physical activity in 338 people of the chemical victims was studied. Sampling was in systematic model. Physical activity was measured using the global physical activity questionnaire (GPAQ) that evaluate work, recreational, transport and sitting activities with interview method. BMI studied in three groups include <25, 25-30, & >30 and the physical activity compared between them. Results: 38.1 percent of study samples have BMI < 25, 46.5 percent have BMI 25-30 and 15.4 percent have BMI >30 kgm2. Metabolic equivalent in the obese group significantly decreased compared with other groups (p=0.04). A significant difference was found in terms of transport related physical activity min/week in BMI > 30 kg/m2, but there was no significant difference in work & recreational activities. In all section, physical activity decreased in obese peoples. Conclusion: Considering the association between physical activity & body mass index and it's important in chemical victimchr('39')s health, discover solutions that in addition to weight control, promoting those physical activities.